Epidural analgesia and vacuum-assisted delivery in primiparous women: maternal and neonatal outcomes. (12th December 2022) - Lang Ben Nun, Eyal; Sela, Hen Y.; Ioscovich, Alexander; Rotem, Reut; Grisaru-Granovsky, Sorina; Rottenstreich, Misgav
Abstract: Objective: We aimed to evaluate the effect of epidural analgesia (EA) on maternal and neonatal outcomes. Methods: We conducted a retrospective cohort database study on primiparous women who underwent a vacuum-assisted delivery (VAD) trial between 2005 and 2019 at a university-affiliated tertiary medical center. We compared women with and without the standard "one protocol" patient-controlled EA. The primary outcome was VAD failure. Secondary outcomes were maternal and neonatal morbidities. We performed univariate analysis, followed by multivariable logistic regression analysis to control for potential confounders. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were calculated. Results: Overall, 7042 primiparous women attempted VAD during the study period; 6238 (88.3%) and 804 (11.7%) women used and did not use EA, respectively. The VAD failure rate was significantly lower among women with than without EA use (2.5% vs. 4.2%, respectively, p < .01). On multivariable analysis, EA use was found to reduce the VAD failure rate (aOR, 0.05; 95% CI [0.01–0.49], p = .01). Notably, EA use was not associated with an increased rate of any maternal or neonatal adverse outcome (aOR, 1.01; 95% CI [0.8–1.27], p = .95 or aOR, 1.14 95% CI [0.89–1.45], p = .3, respectively). Conclusions: EA use in primiparous women is associated with lower rates of VAD failure without an increase in adverse maternal or neonatal outcomes.